Elevated CO2 boosts reproduction and alters selection in northern but not southern ecotypes of allergenic ragweed. Issue 9 (2nd October 2017) - Stinson, Kristina A.; Albertine, Jennifer M.; Seidler, Tristram G.; Rogers, Christine A.
Abstract : PREMISE OF THE STUDY: Many plants increase reproduction in response to rising levels of atmospheric CO2 . However, environmental and genetic variation across heterogeneous landscapes can lead to intraspecific differences in the partitioning of CO2 ‐induced carbon gains to reproductive tissue relative to growth. METHODS: We measured the effects of rising atmospheric CO2 on biomass allocation in the allergenic plant Ambrosia artemisiifolia (common ragweed) across a geographic climate gradient. We grew plants from three latitudes at 400, 600, and 800 µL·L −1 CO2 and analyzed biomass allocation and natural selection on flowering phenology and growth. KEY RESULTS: Both the latitude of origin and CO2 treatment had significant effects on allocation and on estimates of selection. Northern plants were under stronger selection than southern plants to flower quickly, and they produced larger seeds and more reproductive mass per unit of growth. Northern plants were under stronger selection than southern plants to flower quickly, and they produced larger seeds and more reproductive mass per unit of growth. While all plants grew larger and produced heavier seeds at higher CO2, only northern plants increased male flower production. Both size and time to flowering were under selection, with a relaxation of the size–fitness function in northern ecotypes at high CO2 . CONCLUSIONS: Northern ecotypes allocate more CO2 ‐induced carbon gains to reproduction than do southern plants, pointing to a geographic gradient in future pollen and seed production by this species arising from local adaptation. Relaxed selection on size at elevated CO2 could amplify reproductive enhancements to northern ecotypes, although more growth and seed provisioning can be expected overall. Our results demonstrate potential for ecotypic divergence in ragweed responses to climate change.